2019
DOI: 10.1161/jaha.119.014253
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Efficacy of His Bundle Pacing or Left Bundle Pacing Combined With Atrioventricular Node Ablation in Patients With Persistent Atrial Fibrillation and Implantable Cardioverter‐Defibrillator Therapy

Abstract: Background Persistent atrial fibrillation may lead to a higher probability of inappropriate shocks in heart failure patients with an implantable cardioverter‐defibrillator ( ICD ). The aim of this study was to evaluate the impact of His‐Purkinje conduction system pacing combined with atrioventricular node ablation in improving heart function and preventing inappropriate shock therapy in these patients. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 33 publications
2
55
0
2
Order By: Relevance
“…Conduction system pacing combined with AV node ablation showed a high success rate in persistent atrial fibrillation patients with heart failure and implantable cardioverter-defibrillator indication. 10 This study also showed significant improvement in LV function and reduction in inappropriate shocks.…”
Section: Discussionsupporting
confidence: 61%
“…Conduction system pacing combined with AV node ablation showed a high success rate in persistent atrial fibrillation patients with heart failure and implantable cardioverter-defibrillator indication. 10 This study also showed significant improvement in LV function and reduction in inappropriate shocks.…”
Section: Discussionsupporting
confidence: 61%
“…His‐Purkinje system conduction pacing combined with AVN ablation has become an established method of treating drug‐resistant supraventricular arrhythmias, especially in atrial fibrillation patients with heart failure who suffer from insufficient or intolerable medical therapy or failed AF catheter ablation to restore sinus rhythm 4‐7 . As reported previously, pacing in the distal His bundle or left bundle branch region allows for adequate space to safely perform AVN ablation 5,7 . We implanted the pacing lead immediately beyond the tricuspid valve, which was confirmed by contrast ejection though the sheath and echocardiography (Figure 1C).…”
Section: Discussionmentioning
confidence: 95%
“…14,15 LBBP was also used in patients of atrioventricular node ablation with persistent atrial fibrillation and implantable cardioverter-defibrillator therapy in order to improve LV function. 16 In this study, we encountered an interesting case with atrial fibrillation, III AVB and symptoms of heart failure including dyspnea and decreased activity tolerance. After being upgraded to LBBP using a 3830 pacing lead, the patient's symptoms of heart failure alleviated, and the NYHA heart function class improved from class III to class II about 1 month after operation (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%